2015
DOI: 10.1111/jvim.12565
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Serum Pancreatic Enzymes and Ultrasonographic Findings in Diabetic Cats Without Clinically Relevant Pancreatitis at Diagnosis

Abstract: BackgroundCats with diabetes mellitus can have subclinical pancreatitis but prospective studies to confirm this are lacking. Metabolic control of diabetic cats with pancreatitis is difficult.HypothesisSubclinical pancreatitis occurs in diabetic cats at the time diabetes is diagnosed or might develop during the follow‐up period, hampering diabetic remission.AnimalsThirty cats with newly diagnosed diabetes without clinical signs of pancreatitis on admission.MethodsProspective study. On admission and 2 and 6 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 23 publications
2
31
0
Order By: Relevance
“…To our knowledge, a possible association between incretin‐based treatment and pancreatitis in cats has not been investigated. Previous investigations showed that many cats with DM may have subclinical pancreatitis . In our study, some cats treated with exenatide ER had clinical signs compatible with pancreatitis that included decreased appetite and vomiting, but only 1 (8.3%) cat with normal baseline Spec fPL and DGGR‐lipase concentrations had an increase in Spec fPL concentration during treatment.…”
Section: Discussionmentioning
confidence: 47%
“…To our knowledge, a possible association between incretin‐based treatment and pancreatitis in cats has not been investigated. Previous investigations showed that many cats with DM may have subclinical pancreatitis . In our study, some cats treated with exenatide ER had clinical signs compatible with pancreatitis that included decreased appetite and vomiting, but only 1 (8.3%) cat with normal baseline Spec fPL and DGGR‐lipase concentrations had an increase in Spec fPL concentration during treatment.…”
Section: Discussionmentioning
confidence: 47%
“…Diabetes mellitus in cats often is associated with abnormalities in serum markers of exocrine pancreatic disease . A weak positive correlation between feline pancreatic lipase activity (fPLI) and serum fructosamine was reported in cats with DM, suggesting that subclinical pancreatitis might cause inadequate glycemic control .…”
Section: Dm Secondary To Diseases Of the Exocrine Pancreas In Catsmentioning
confidence: 99%
“…Alternatively, inadequate glycemic control (reflected by increased serum fructosamine) might cause ongoing damage to the exocrine pancreas (reflected by increased fPLI), as suggested by an experimental study in which pancreatic neutrophils increased in healthy cats with experimentally induced hyperglycemia . The fact that most diabetic cats with increased fPLI do not have gastrointestinal signs and are not less likely to achieve remission further argues in favor of inadequate glycemic control as the cause of increased fPLI . Similarly, T2DM in people is considered a risk factor for pancreatitis .…”
Section: Dm Secondary To Diseases Of the Exocrine Pancreas In Catsmentioning
confidence: 99%
“…The morphologic scoring system 5 used in the present investigation led to diagnose acute or chronic pancreatitis in more than half of the diabetic and control cats, suggesting that pancreatic inflammation is very common in this species. However, identification of pancreatitis is often difficult in living cats, 18 and its clinical diagnosis was achieved in only 1 diabetic cat. Therefore, in light of the large discrepancy observed between the frequency of histopathologic and clinical diagnosis of pancreatitis, the significance of the adopted scoring system 5 remains uncertain, and the term pancreatitis might have been misleading for some cases.…”
Section: Discussionmentioning
confidence: 99%
“…One of our studies revealed that about 60% of diabetic cats (18 of 30) had suspected pancreatitis at the time of initial diagnosis, based on increased activity of serum 1,2-o-dilauryl-rac-glycero-3-glutaric-acid-6 0 -methylresorufin ester lipase, increased feline pancreas-specific lipase activity, or the presence of ultrasonographic abnormalities of the pancreas. 18 In addition, diabetic cats with increased feline pancreas-specific lipase values were less likely to achieve clinical remission of DM, which suggests that glycemic control may be more difficult when pancreatitis is present, despite appropriate therapy. Histopathologic evaluation of the pancreas was not carried out in any of those clinical studies.…”
Section: 18mentioning
confidence: 99%